Phenotypic evaluation of Trifolium repens x Trifolium uniflorum F₁ interspecific hybrids as predictors of BC₁ hybrid progeny : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Plant Breeding at Massey University, Palmerston North, New Zealand - Ebbett, Michelle Anne (Massey University, 2017)
Interspecific hybrids between white clover (Trifolium repens) and its close relatives are being created to address the lack of variation within white clover for traits relating to persistence and drought tolerance. This study addresses two concepts related to developing hybrid breeding strategies using Trifolium repens x Trifolium uniflorum hybrids. A first sandframe experiment investigated whether some of the first generation hybrid plants (F1) with common parents were better than others as future parents. A second experiment assessed whether the performance of the first back cross (BC1) progenies could be predicted from the parental F1 phenotypes. The foliage, fertility, roots and dry weight production of four families of F1 hybrids were evaluated following a period of growth in sand. From each family, the F1 hybrids with the highest and lowest dry weight production were selected and back crossed to two contrasting white clover cultivars. The resulting BC1 hybrid phenotypes were evaluated to ascertain whether any F1 hybrids were markedly better as future parents in hybrid breeding programmes, and whether the F1 phenotype could be used to predict that of the BC1 progeny. Differences in expression of more than half of the traits evaluated were found both between F1 families, and among genotypes within F1 families. Evaluation of the subsequent BC1 generation identified large amounts of variation in expression of most traits both within and among hybrid families. However correlations between trait expression of the F1 parent and the corresponding BC1 progeny were weak to non-existent for most traits evaluated. The absence of correlations indicated that the performance of an F1 hybrid genotype is not able to be used as a predictor of the BC1 progeny phenotypes, and that selection out of the F1 generation is futile in the formation of interspecific hybrid breeding populations.
Keywords: Clover; Hybridisation; White clover; Drought-tolerant plants; Breeding; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Plant breeding